Tratamentos para descontaminação de tomates contendo resíduos de imidacloprido - Bissacotti, Anelise Pigatto (2018)
The tomato is considered a functional food because its nutritional components promote health benefits for humans. However, in recent years, concerns have arisen due to the fact that food present often pesticide residues. During the cultivation period, tomato is susceptible to pests and diseases, and the use of pesticides is one of the methods used to control this problem. Among the pesticides allowed for the tomato crop is the neonicotinoid insecticide imidacloprid, which can cause damage to human health. Thus, this work had as objectives to evaluate the effects of washing on the imidacloprid residues in tomatoes, to determine the estimated daily intake (FDI) of this pesticide, in addition, to divulging methods of decontamination of the fruit to the population. Tested the washing of tomatoes with tap water and solutions of acetic acid at 5, 10 and 15%, chlorinated at 100, 150 and 200 ppm, of sodium bicarbonate at 5, 10 and 15% and of lemon juice at 5, 10 and 15%, followed by a rinse with tap water. The washing were performed in triplicates. Extraction and determination of imidacloprid concentrations in tomatoes were performed by modified mini-Luke method and ultra performance liquid chromatography coupled to mass spectrometry (UPLC-MS/MS), respectively. The pH of washing solutions was checked and the chemical composition of the samples was characterized. At the end, a primer was elaborated describing the most efficient washes in reducing the concentration of imidacloprid in tomato. To estimate human exposure to the imidacloprid pesticide, EDI was determined for Brazilian women, men, adolescents, adults and elderly. Data were analyzed through analysis of variance and Tukey's test, at 5% of significance level. Washing with tap water was the most effective method in reducing imidacloprid in the samples. In contrast, solutions of sodium bicarbonate at 10%, acetic acid at 10% and chlorinated at 150 ppm were the least efficient tomatoes containing imidacliprid decontamination. Considering all different solutions tested, there were no linear decreases in imidacloprid levels as their concentration increased. The samples did not differ in relation to moisture contents, acidity and total soluble solids present in them. The pH of the solutions did not interfere tomatoes pH. The relation of total soluble solids and acidity demonstrated that tomatoes were adequate to the quality standard for consumption. The correlation between the chemical parameters and imidacloprid levels in tomatoes showed that there is no linear relation between these data. Determined EDI have been shown to be below the acceptable daily intake (ADI) established in Brazil, United States of America, Europe and by the Codex Alimentarius. It has been shown that tomatoes analyzed were suitable for human consumption, since they met the parameters for being considered as toxicologically safe.